Christ and History : The Christology of Bernard Lonergan from 1935 to 1982 - Crowe, Frederick E (Book collections on Project MUSE., 2015)
Crowe presents the evolution of Lonergan's thinking on Christology in the context of the radical developments contained within his other theological writings.